Mapping Point Defects of Brookite TiO2 for Photocatalytic Activity Beyond Anatase and P25 - Khan, Sovann; Je, Minyeong; Kim, Donghun; Lee, Seungwoo; Cho, So-Hye; Song, Taeseup; Choi, Heechae (American Chemical Society, 2020)
Brookite, the least studied crystalline phase of TiO2 recently has been found to have excellent photocatalytic activities, comparable to that of anatase TiO2. However, its activity is highly dependent on its defect levels. We systematically studied the equilibria of the native point defects of brookite, along with their effects on photocatalytic activities. From first-principles calculations and thermodynamics modeling, we predicted the formation of an interstitial defect (Ti-i(4+)) under weak reductive conditions while that of Ti-O(4+) under strong reductive conditions. Our calculations also suggest that Ti-i(4+) exclusively induces ideal shallow defect levels in brookite, but Ti-O(4+) results in deep level formations. In our experiments, we demonstrated that the moderately reduced brookite TiO2 sample has the best photocatalytic activity. This combined theoretical and experimental work explains the inconsistent photocatalytic activities of brookite and suggests the processing conditions that yield highly active brookite photocatalysts-one that is comparable to or exceeding that of anatase.
Keywords: GENERALIZED GRADIENT APPROXIMATION; SELF-DOPED TIO2; COMPUTATIONAL PREDICTIONS; RUTILE; TRANSFORMATION; ABSORPTION; REDUCTION; HYDROGEN; ENERGY; OXIDE